Avaliação da mastite e seu impacto sobre a sensibilidade à dor em vacas leiteiras - Peters, Mônica Daiana de Paula (2012)
This thesis presents two studies about evaluation of different levels of mastitis and their treatments besides analyzing the corresponding pain responses in dairy cows. The first study is about the effects of mastitis levels upon somatic cells count, pain thresholds and acute phase proteins concentration (APP): serum amyloid A (SAA) and fibrinogen. One hundred lactating cows were evaluated with different mastitis levels, being classified as follows: level zero (healthy cow), level 1 (subclinical mastitis first degree), level 2 (subclinical mastitis second degree), level 3 (subclinical mastitis third degree), level 4 (clinical mastitis). SCC of the milk from cows affected with clinical mastitis is significantly higher than milk from cows with subclinical mastitis at different levels, as well as healthy cows. Sensibility to pain is similar among clinical and subclinical mastitis, but cows presenting clinical mastitis show lower resistance to pain than healthy cows. Pain threshold measured in the hind limbs (right or left) is not affected by affected mammary gland side. Acute phase proteins (SAA and fibrinogen) are not affected by absence or occurrence of mastitis. The second study evaluated the non steroid anti-inflammatory (AINE) ketoprofen associated to antibiotic upon pain sensibility of cows affected by clinical mastitis. The pain threshold measured on the period without treatment was significantly lower than in the first day after beginning of the treatment, which was similar to the threshold measured on the second day after the beginning of the treatment, which was similar to that measured before the treatment. Variability in pain threshold among cows was larger at the period before the beginning of treatment, but it decreased on the first day after the beginning of the treatment. Cows with clinical mastitis and treated with AINE show reduction in pain sensibility just on the first day after the beginning of the treatment. Clinical mastitis cause pain in dairy cows, being needed more researches aimed at adoption of an efficient treatment to decrease pain sensibility to increase animal welfare.